The Effect of Using the Sipenyu Application on the Effectiveness of Population Administration Services in the Covid-19 Pandemic Era in Berau Regency 2021 - Nafrah Maudina; Bella Kharisma; Dian Eka Rahmawati (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2022)
In the current era, the digitalization system is highly utilized both in terms of communication and information that is used to assist the work of government agencies in meeting the needs of the community, namely the fulfillment of public services. the community with government agencies and previous service systems still have problems that prolong service delivery times and are less effective, therefore the application of a digitalization system is a solution to overcome these problems. This problem also occurs in BERAU Regency in population administration services, so DISDUKCAPIL implements the SIPENYU application as a solution to the service problem. The purpose of this study is to reveal hypotheses related to the influence and factors that support the use of the SIPENYU application in realizing the effectiveness of administrative services in the BERAU Regency. The findings of this study are that there is a significant effect related to the use of the SIPENYU application on the effectiveness of population administration services and this is evidenced by hypothesis testing with measurement indicators, namely Performance Expectancy, Effort Expectancy, Social Influence, on Perceived Enjoyment. on service effectiveness.